If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3(x + -4) = -5 + 4x + 13 Reorder the terms: 5x + -3(-4 + x) = -5 + 4x + 13 5x + (-4 * -3 + x * -3) = -5 + 4x + 13 5x + (12 + -3x) = -5 + 4x + 13 Reorder the terms: 12 + 5x + -3x = -5 + 4x + 13 Combine like terms: 5x + -3x = 2x 12 + 2x = -5 + 4x + 13 Reorder the terms: 12 + 2x = -5 + 13 + 4x Combine like terms: -5 + 13 = 8 12 + 2x = 8 + 4x Solving 12 + 2x = 8 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 12 + 2x + -4x = 8 + 4x + -4x Combine like terms: 2x + -4x = -2x 12 + -2x = 8 + 4x + -4x Combine like terms: 4x + -4x = 0 12 + -2x = 8 + 0 12 + -2x = 8 Add '-12' to each side of the equation. 12 + -12 + -2x = 8 + -12 Combine like terms: 12 + -12 = 0 0 + -2x = 8 + -12 -2x = 8 + -12 Combine like terms: 8 + -12 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| (x+8)(x-7)=16 | | 0=-16t^2+20t+40 | | -4w-4= | | 99-4s-6s=-9 | | 9=b | | y=xcos(x) | | 2+2=8b | | 2x-5(x-5)=-4+3x+17 | | =2(x+y)+9x+6y | | 42=3(2-6h) | | z+8(z-4)=-4 | | 2x^2-9x-12=0 | | 77-7x=11x+19 | | 6x=24+3x | | B=58b | | 3(m+5)=39 | | S=6-3 | | c-80=36 | | X=38-(-x) | | 3(x+4)-(x+5)=x+4 | | =7+4(x+5) | | f=6q-4 | | -23b=35b | | .23x+.45=8-.32x | | 3x+-7+2x=9 | | 3x-8=5x+3 | | 18x^2-25x=-8 | | 0=-16t^2+60 | | (24)5= | | =7x+4(x+5) | | 4(x-6)+4=6x-8 | | 2r^2+18r+33=0 |